Testing and analysis of masonry hollow clay block prisms filled with mortar. (30th May 2019) - Nascimento, Marcio R.; Roman, Humberto R.; Fonseca, Fernando S.
In some design situations, in construction systems with structural masonry, an increase in the capacity of the walls is required, which can be achieved with the filling of empty cells of masonry blocks with grout. The Brazilian technical standard for clay masonry blocks aiming at attaining greater agility and flexibility in the construction process allows the use of bedding mortar instead of grout to fill the cells of the blocks. In this context, the objective of this study was to evaluate the mechanical behaviour of prisms filled with bedding mortar. Six classes of mortar and one type of clay block with nominal resistance of 6 MPa were studied. The results of the compressive strength of the prisms indicate the viability of using bedding mortar with the same structural function as grout. This article presents also an analytical study to evaluate the mechanical behaviour of clay block prisms filled with mortar. Analyses were conducted using general-purpose, nonlinear finite element software that simulates structural behaviour under different loading scenarios. A three-dimensional model of the prisms was developed using eight-node brick elements for both block and mortar with nonlinear properties assigned to each material.